Late Glacial and postglacial seismicity in the Northeastern Fennoscandian Shield: tectonic position and age of paleo-earthquakes near Murmansk - Svetlana B. Nikolaeva; Mikhail V. Rodkin; Sergey V. Shvarev (Bulletin of the Geological Society of Finland, 2021)
Earthquake-induced deformations located near Murmansk City were investigated for information on the age, tectonic position and spatial occurrence of paleo-earthquakes. The main earthquake-generating zone is identified to be the system of strike slip faults and reverse-oblique faults trending NNW along the Kola River valley. We used radiocarbon analysis and paleogeographic reconstructions and revealed three episodes of increased seismic activity: from 9500 to 10 500 cal BP, from 892 to 1182 cal BP, and from 200 to 300 cal BP. Based on the peak ground velocity estimation method we suggest that an earthquakes with a maximum moment magnitude up to Mw ≈ 6.0–6.5 may have taken place in the studied area. The recorded location of seismogenic deformation near faults indicates area of strong Late Glacial and Holocene earthquakes occurring in the northern Kola Peninsula; this is also consistent with observations concerning the historical events of 1772 and 1873, which took place near the area. Combined with previous data on palaeoseismicity in Kola region, our studies indicate a longer lasting and more complex spatial and temporal history of postglacial seismicity in the Northeastern Fennoscandian Shield area. In contrast to the generally accepted opinion, strong seismic events occurred not only during the deglaciation period or immediately after it, but continued until the late Holocene and the last centuries. Glacial isostasy as a factor giving rise to stresses has become minimal by the present time, while the tectonic factor continues to be felt.